2022
DOI: 10.1097/md.0000000000030751
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic assessment of root canal morphology of mandibular central incisors using new classification system: A cross-sectional study

Abstract: Lack of basic knowledge about the external and internal anatomies of the root canal system and common variations in teeth may lead to various procedural errors or treatment failure. In this study, the root canal configurations of mandibular incisors and the symmetry of the contralateral incisors of Saudi Arabian subpopulations were analyzed and determined using cone beam computed tomography (CBCT). A retrospective evaluation of 700 patients was conducted, and 1260 fully developed permanent mandibular central i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“… It was evident from the results that Saudi population commonly had more than one canal and bilateral symmetry was more in central incisor than lateral incisor with respect to number of roots, canals and their configuration type. [ 53 ] Alobaid, M.A., et al 2022 1260 Mandibular central incisors KAVO OP 3D Pron (KaVo Dental, Charlotte, NC, USA) 0.85 mm On demand 3DTM imaging software (Cybermed Inc., Unit K Tustin, CA) New system of classification Retrospective data from database All the right and left lower central incisors were single rooted on both the sides. Canal configuration in left central incisor: Male: 80.2% were (1-1-1), 13.6% had (1-2-1), 2.2% had (1-1-2), 3.7% had (1-2-2), and 0.4% were (2-2-1).…”
Section: Resultsmentioning
confidence: 99%
“… It was evident from the results that Saudi population commonly had more than one canal and bilateral symmetry was more in central incisor than lateral incisor with respect to number of roots, canals and their configuration type. [ 53 ] Alobaid, M.A., et al 2022 1260 Mandibular central incisors KAVO OP 3D Pron (KaVo Dental, Charlotte, NC, USA) 0.85 mm On demand 3DTM imaging software (Cybermed Inc., Unit K Tustin, CA) New system of classification Retrospective data from database All the right and left lower central incisors were single rooted on both the sides. Canal configuration in left central incisor: Male: 80.2% were (1-1-1), 13.6% had (1-2-1), 2.2% had (1-1-2), 3.7% had (1-2-2), and 0.4% were (2-2-1).…”
Section: Resultsmentioning
confidence: 99%
“…After removal of duplicates, a total of 229 were screened. Studies not related to root and canal anatomy were excluded leaving a total of 15 studies that fulfilled the inclusion criteria [8,17,18,[21][22][23][24][25][26][27][28][29][30][31][32]. The PRISMA 2000 flowchart summarises the search strategy (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Tables 1-5 summarise the details of the included studies. Out of the 15 studies, three examined the anatomy of maxillary anterior teeth in patients (CBCT clinical studies) (21)(22)(23), five examined mandibular anterior teeth (four clinical CBCT (21)(22)(23)(24), and one ex vivo micro-CT (25) on extracted teeth), four studies examined maxillary premolar teeth (three clinical CBCT (18,26,27), and one ex vivo CBCT (17) on extracted teeth), two studies examined mandibular premolar teeth (one clinical CBCT (29), and one ex vivo micro-CT (28) on extracted teeth) and three studies examined maxillary molar teeth (clinical CBCT) (30)(31)(32). Interobserver agreement (Cohen's k) scores performed for selection of studies was calculated as 0.871-almost perfect agreement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, it was found that perceived usefulness, ease of use, security, and privacy were significant antecedents of customer attitudes toward using internet banking. A study performed in the context of crisis response strategy found a significant mediating role of online brand attitude and online purchase intention [ 54 , 55 , 56 , 57 , 58 , 59 ]. The study also found that brand-perceived usefulness significantly strengthens the positive relationship between online brand attitude and online purchase intention.…”
Section: Introductionmentioning
confidence: 99%